Barriers to hand hygiene compliance in intensive care units during the COVID-19 pandemic: A qualitative study - Maryam Ahmadipour; Mahlagha Dehghan; Mahlagha Dehghan; Mehdi Ahmadinejad; Maryam Jabarpour; Parvin Mangolian Shahrbabaki; Zahra Ebrahimi Rigi (Frontiers Media S.A., 2022)
BackgroundThe practice of hand washing is an effective way to prevent contamination and disease transmission. Following the COVID-19 pandemic, hand washing has become increasingly important. Therefore, this qualitative study aimed to understand barriers to hand hygiene compliance among healthcare workers during the COVID-19 pandemic.Materials and methodsTwenty-five healthcare workers from intensive care units were sampled using purposive sampling in a qualitative content analysis study. Data were collected through a semi-structured interview and field notes. Based on the Lundman and Graneheim approach, the data were analyzed. COREQ checklist was used to report the research.ResultsAccording to the findings, there are three main categories of barriers to hand hygiene practice: barriers related to individuals (including two subcategories of lack of knowledge of healthcare workers and healthcare workers' improper attitude), barriers related to management (including two subcategories of wrong behavioral patterns and unsuitable training and planning), and barriers related to organizations (including four subcategories of heavy workloads, improperly designed wards, a lack of equipment, and lack of quality equipment).ConclusionsThis research indicates that hand washing practice increased during the COVID-19 pandemic. Nevertheless, some barriers persist, resulting in a decline in hand washing compliance among health care workers. This finding can help managers and policymakers remove barriers to hand washing compliance and improve healthcare workers' adherence to hand washing.